Meget fjern læsning. Litteraturen, de store data og Google Ngrams - Thomsen, Mads Rosendahl (Passage - Tidsskrift for litteratur og kritik, 2013)
Mads Rosendahl Thomsen: “Very Distant Reading. Literature, the Big Data, and Google Ngrams” The article discusses the uses of Google Ngram Viewer in light of the current larger interest in digital humanities. Through a series of examples, the article seeks to demonstrate how Ngrams are useful for providing a better context for otherwise more intuitive notions of cultural importance of works and how the tool can help generate new research questions, both with regards to the position of literary works in culture and with regards to the differences between the literary world and culture at large.